Elk1 and AP-1 sites in the TBP promoter mediate alcohol-induced deregulation of Pol III-dependent genes - Zhong, Qian (2013)
The major risk factors for hepatocellular carcinoma (HCC) are chronic liver diseases that include hepatitis B, hepatitis C, alcoholic liver disease and non-alcoholic steatohepatitis. However, the mechanisms of alcohol-associated HCC remain to be elucidated. The products of RNA Pol III (RNA polymerase III) dependent genes are elevated in both transformation cells and tumor cells. TBP (TATA-box binding protein) is a central transcription factor, which regulates Pol I, Pol II and Pol III gene activity. Our studies have demonstrated that alcohol increases TBP expression and Pol III gene transcription to promote liver tumor formation. We continue to investigate how ethanol mediates TBP expression. Here, we report that ethanol induces TBP promoter activity and the induction is ethanol dose dependent. Blocking the JNK1 pathway by a chemical inhibitor and siRNA reduce this ethanol-induced activity. Furthermore, mutating G>A at a −46bp Elk1 binding site of the TBP promoter or mutating AP-1 binding site at −37bp (A>G) and −38bp (C>T) reduces the TBP promoter activity. Mutation of both Elk1 and AP-1 binding sites dramatically represses this induction. Together, these studies demonstrate that, for the first time, alcohol increases Pol III gene transcription through a response element, which is composed of the overlapping the Elk1 and AP-1 binding sites of the TBP promoter. It suggests that these binding sites may play a critical role in alcohol-induced deregulation of Pol III genes in liver tumor development.